THE IMPLEMENTATION OF VALUES IN THE BELIEF IN GOD AS THE ALMIGHTY AS AN BASIS OF ANTI – CORRUPTION EDUCATION - Elly Malihah, Subelo Wiyono, Cecep Darmawan (Jurnal Civicus, 2015)
Religious values already owned Indonesian nation long before the proclamation of August 17, 1945. Before the entry of religion into the public Nusantara Indonesia already have the confidence to fulfill his spiritual side as human beings, in the form of trusting belief in spirits (anismime) which is one reflection of that spiritual values of Indonesian society has been formed long before the influence of religion entering into the archipelago. Anti-corruption education should make the implementation of theories of value is derived from the theory of the "golden rule" as a basis. Research on the Implementation of Values on God as an Elementary Education Against Corruption (Descriptive Study of Madrasah Tsanawiyah Negeri Fakfak and Madrasah Tsanawiyah Muhammadiyah Fakfak) is using a qualitative approach. In this study, researchers hope to find the existence of such realism is believed to Kant, a transcendental idealism. Through observation and interviews that the researcher did and came to the conclusion how the implementation of values on God as the basis of anti-corruption education.Â